ALQURAN SEBAGAI SUMBER EPISTEMOLOGI - Muh Ilham (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2018)
In the midst of debates of scientists about the nature of science, character and source, this article reveals that the Koran is an epistemological source that cannot be doubted by its truth. By tracing thematic functions and verses by analyzing them in the framework of philosophical interpretation, it is found that the Koran is very intense calling on thinking, pondering, doing research and of course reading. At the same time, the Koran indicates that science is essentially all from God. There is no separation between religion and general science. In addition, the source of knowledge is not only limited to the five senses alone, but there is knowledge that comes from a clean heart through a spiritual process. Science is known as ladunni, this concept is what distinguishes the Koran as a source of epistemology with the concept of epistemology introduced by Western scientists